Evaluation of production efficiency and waste management in the Pak Imam tofu and tempeh industry using cleaner production methods - Mujayyanah, Zuhrotul; Suroso, Erdi; Utomo, Tanto Pratondo; Suharyono, Suharyono; Hidayati, Sri; Nurmaisari, Melda (Jurusan Teknologi Hasil Pertanian Universitas Mulawarman, 2026)
The Imam's tofu and tempeh industry in Central Lampung Regency produces two main types of products: tofu and tempeh. Additionally, the industry processes tofu dregs into a third product, gembus tempeh. This study aimed to identify the production performance and waste management of Imam's tofu and tempeh industry using the quick scan method. The data used are in the form of primary data and secondary data. The data obtained are presented in the form of mass balances and graphs. The research results show that improvements need to be made in the aspects of technology, management, production processes, and waste management. Water consumption in the Pak Imam industry is still relatively high, that is, 2,251.68 liters per day. This has an impact on the high volume of waste produced, which is 2,119.98 liters per day. Potential waste that has not been optimally utilized is found in the crushing stage (tempeh production) and extraction stage (tofu production). It is necessary to carry out maintenance on waste storage ponds due to silting. In addition, there are problems with the cleanliness of the place and equipment, so that the resulting product is less hygienic.